Tool responsive regions in the posterior parietal cortex: Effect of differences in motor goal and target object during imagined transitive movements - Vingerhoets, Guy; Acke, Frederic; Vandemaele, Pieter; Achten, Eric (NeuroImage (Orlando, Fla.), 2009)
Neuroanatomical and functional studies have proposed a functional segregation of the human dorsal stream into a dorso-dorsal pathway, believed to serve as an object-independent stream involved with on-line control of action, and a ventro-dorsal pathway that provides conceptual input guiding the functional manipulation of objects. We aim to evaluate whether the inferior parietal cortex deals specifically with action reliant on stored knowledge. Fifteen right-handed, normal volunteers varied the intention of their transitive movements by imagining their dominant arm and hand pointing to, grasping to move, grasping to use, or grasping and using three-dimensional representations of target objects depicting graspable neutral shapes, unfamiliar tools, and familiar tools. Imagined movements intended to make functional use of familiar objects revealed increased activation in the left inferior parietal lobule. Compared to gestures aimed at displacing an object, functional (use) intentions elicited activation in the anterior and middle portions of the lateral bank of the intraparietal sulcus, suggesting involvement in the higher order control of action. Compared to functionally unfamiliar objects, grasping movements aimed at familiar tools activated the convex portion of the inferior parietal lobule, suggesting a role for the ventro-dorsal stream in object-selectivity. These data confirm that stored knowledge for the skillful manipulation of familiar tools of right-handed volunteers is predominantly located in the left inferior parietal lobule, and further suggest that tool use-responsive regions and tool object-responsive regions are not identical, but may form a local network in which different nodes contribute differently to the representation of functional tool use in humans.